Patterns of Deterioration in Moderate Patients With COVID-19 From Jan 2020 to Mar 2020: A Multi-Center, Retrospective Cohort Study in China - Chen, Sheng-long; Feng, Hui-ying; Xu, Hui; Huang, Shan-shan; Sun, Jiu-feng; Zhou, Lin; He, Jun-lei; Song, Wen-liang; Wang, Rui-jie; Li, Xin; Fang, Ming (Frontiers in Medicine, 2020)
Background: Around the globe, moderate cases account for the largest proportion of all COVID-19 patients, and deteriorated moderate patients contribute the most in mortality. However, published articles failed to address the deterioration details of moderate case, especially on when and how they deteriorated. Methods: All moderate COVID-19 patients hospitalized in Guangdong Province from Jan 14th to Mar 16th, 2020 were included in this multi-centre, retrospective, cohort study, and were divided into deteriorated and non-deteriorated groups according to clinical status. Demography, symptoms, therapy and laboratory characteristics were collected to explore the features of disease deterioration. Results: Of 1168 moderate patients included, 148 (13%) deteriorated to severe (130 cases) or critical (18 cases) status. Over 20% of the older subgroup (＞50 years old) showed deterioration. The median time for deterioration was 11 days after onset (IQR 9-14). 12.2% severe cases could further develop to critical status after 3 days (IQR 2-6.5) of having severe condition. Respiratory dysfunction and hypoxia were the major manifestations as disease deterioration, while 76 cases (52.1%) showed respiratory rate >30 breaths/min, 119 cases (80.4%) showed SaO2<93%, 100 cases (67.5%) had 201